Psychological Drivers of Consumer Boycott: Understanding Emotional and Social Identity Influences in Batam - Ulfah, Mutia; Sabrina, Nova; Putri, Ancala Laras (Journal of Applied Business Administration, 2025)
Consumer boycotts have become an increasingly significant form of consumer activism, driven by ethical, political, and social concerns. This study explores the psychological motivations behind boycott participation in Batam, focusing on emotional triggers, social identity influences, and perceived effectiveness. Using a qualitative approach, data were collected through in-depth interviews and focus group discussions with 30 respondents from Generation X, Y, and Z. Thematic analysis was conducted manually, highlighting key motivations such as moral responsibility, peer influence, and digital activism. The findings reveal that Gen Z engages in boycotts as an expression of online activism, Gen Y is driven by ethical consumption, and Gen X remains skeptical and pragmatic. This research contributes to the literature on consumer activism, ethical consumption, and social identity theory, offering insights for businesses, policymakers, and advocacy groups on how to navigate boycott movements and maintain consumer trust.